2005
DOI: 10.1001/archopht.123.1.71
|View full text |Cite
|
Sign up to set email alerts
|

Posterior Capsule Opacification in Mice

Abstract: To present a new model of posterior capsule opacification (PCO) in mice.Methods: An extracapsular lens extraction was performed in 28 consecutive mice. Animals were humanely killed 0 and 24 hours and 3 and 14 days after surgery. Eyes were enucleated and processed for light microscopy and immunohistochemistry.Results: In 20 animals (71%), the eye appeared well healed before death. In 8 animals (29%), postoperative complications were noted. All animals developed PCO 2 weeks after surgery. Immediately after extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 22 publications
1
15
0
Order By: Relevance
“…Use of laryngeal masks to secure airways of some avian patients may prevent occurrence of postintubation tracheal stricture. 39 PCO was the most commonly reported postoperative complication in this study (4/18 eyes, 22.2%), which is also reported to be the most common complication of cataract surgery in humans 26 and domestic canids. 2, 36 Most other postoperative complications of cataract surgery in this study were mild and transient, but two birds were found to have decreased vision approximately 1 yr after surgery.…”
Section: Discussionsupporting
confidence: 61%
“…Use of laryngeal masks to secure airways of some avian patients may prevent occurrence of postintubation tracheal stricture. 39 PCO was the most commonly reported postoperative complication in this study (4/18 eyes, 22.2%), which is also reported to be the most common complication of cataract surgery in humans 26 and domestic canids. 2, 36 Most other postoperative complications of cataract surgery in this study were mild and transient, but two birds were found to have decreased vision approximately 1 yr after surgery.…”
Section: Discussionsupporting
confidence: 61%
“…In addition, the manner of fibre cell removal, which requires pushing the eye cavity with forceps could be potentially more traumatic than clinically employed methods. An advance on this method was described by Lois et al (2005a) who performed simulated cataract surgery on mice, which included continuous curvilinear capsulorhexis and removal of lens fibres by hydroexpression. Using these methods, cell proliferation, migration and differentiation have been observed following surgery.…”
Section: Murinementioning
confidence: 99%
“…In addition, there was evidence of weak aSMA expression, which suggests some degree of transdifferentiation may occur in the mouse following injury. It would therefore be of interest to know whether levels would increase with Moreover, Lois et al (2005a) also observed capsular wrinkling that causes light scatter. The Call method has been used to identify gene expression patterns associated with epithelial to mesenchymal transition and lens differentiation using gene microarrays over a three week experimental period (Medvedovic et al, 2006).…”
Section: Murinementioning
confidence: 99%
“…The culture conditions can therefore be carefully controlled and thus interpretation of the data is easier than in more complex systems. In addition to these in vitro methods, in vivo animal models have been developed [35][36][37] and it is probable that transgenic animals will be studied further to determine PCO progression. A number of features are common to both ASC and PCO, and not surprisingly TGFb is again strongly implicated [21].…”
Section: The Lens: a Model For Fibrosismentioning
confidence: 99%